36.7k views
5 votes
Use the quadratic formula to solve the equation. If necessary, round to the nearest hundredth. −5y2 + 2y = −2

User Kwerle
by
5.9k points

2 Answers

3 votes

Answer:

y1=-0.46

y2=0.86

Explanation:

User MeatPopsicle
by
5.7k points
4 votes
1. The quadratic formula is applied to solve quadratic equations. This is:

y=(-b±√(b²-4ac))/2a

2. Therefore, you have:

−5y²+2y=−2
−5y²+2y+2=0

a=-5
b=2
c=2

3. When you substitute these values into the quadratic formula, you obtain:

y=-2±√(2²-4(-5)(2))/2(-5)
y=-2±√44/-10

4. Therefore, you have:

y1=-0.46

y2=0.86


User Mahmoud Jorban
by
6.6k points